Impacts of extreme events in the submedium of the São Francisco river basin - Marques, E. A. T.; Oliveira, C. R.; Cardoso, A. S.; Sobral, M. C. (Seven Editora, 2023)
The Submiddle San Francisco River Basin (SSFB), located in the semi-arid region, is subject to adverse hydrological conditions, increasing the levels of vulnerability of the local population to climatic phenomena and favoring natural disasters such floods and severe droughts and the risk of water shortages in its reservoirs. This critical scenario has been worsened due to climate change. In most cases, the impacts related to the occurrence of such phenomena can be amplified due to the lack of planning and structure. In this context, the objective of this study was to identify the impacts associated with climate change on the SSFRB. To identify critical climatic periods, the Standardized Precipitation Index (SPI) was used during the period 1970-2014. It was observed that despite the existence of wetter years, there was a negative trend of precipitation over the studied period. Despite the occurrence of these events, drought episodes were more frequent, mainly from the 1990s onwards, with emphasis on the years 1993 and 2012, classified as extremely dry. These extreme events, which have been intensified in recent decades, cause severe social, economic and environmental impacts, intensifying social conflicts. Public policies should be the priority for the prevention and minimization of these impacts, such as revitalization of the basin, protection of springs, sanitation of municipalities, erosion control, establish flood prevention, protection of the floodable areas, reduction of losses in water distribution, rational use of water resources, among other measures. DOI: https://doi.org/10.56238/tfisdwv1-042